Post thoracotomy spinal cord compression in a child. A word of caution - Kanakis, Meletios A. (Elsevier, 2013)
INTRODUCTION: Oxidised regenerated cellulose is a commonly used haemostatic agent in surgery which, in rare cases, has been held responsible for severe complications. PRESENTATION OF CASE: A 6-year-old girl developed flaccid paraplegia following the excision of a large thoracic ganglioneuroblastoma. Magnetic resonance imaging revealed spinal cord compression at the T10–11 level and the patient underwent emergency decompression via the previous thoracotomy. At operation the causative factor was found to be a mass consisted of cellulose used at the original procedure to control local bleeding in the vicinity of the intervertebral foramen. DISCUSSION: The accessibility of the spinal canal from the thoracic cavity through the opening of the intervertebral foramen may allow migration of material and in this case oxidized regenerated cellulose, commonly used during cardiothoracic procedures, can cause rare but severe complications such as compression of the spinal cord. CONCLUSION: The value of hemostatic gauze is well established in cardiothoracic surgery. However, surgeon should be cautious with the application of material in the proximity of the intervertebral foramen, especially if this is to leave behind after the completion of the procedure.